STRATEGI PENGEMBANGAN POLA KEMITRAAN ANTARA PENGUSAHA PERIKANAN DENGAN NELAYAN TRADISIONAL YANG BERMITRA DI PESISIR PANTAI NAMOSAIN, PANTAI PASIR PANJANG, DAN PANTAI OESAPA KUPANG - S. Marjaya; Crish Namah; Krisna Setiawan (Partner, 2008)
Strategy for Developing Pattern of Partner between Fishery Entrepreneur and Traditional Fisherman Having Partner in Namosain, Pasir Panjang, and Oesapa. This research was to identify internal and external factors in the form of weakness and strength, threat and opportunity experienced by fishery entrepreneurs with traditional fishermen in the effort of developing partner pattern, and to formulate strategy in the effort of developing partner pattern among fishery entrepreneurs and traditional fishermen in partner. The research used analysis of Strength Weakness Opportunity Treat to find out internal factors in the form of strength, weakness, and external factors in the form of threat and opportunity to fishery entrepreneurs and traditional fishermen, and to determine alternative strategy used matrix of SWOT. The result showed that internal strategy factors representing weakness and strength in development of partner pattern. Those were education level of responders pertained were still lower (52% SMU); the skill and knowledge in the field of fishery was including low category with cumulative score performance 70,00; the capital employed was still very less with mean of Rp. 3-6 million in 3-7 days; and the ability read good enough opportunity. While, external strategy factor in developing of partner pattern representing threat and opportunity cover; very big oceanic potency, production, price, and high request, availability of local market and adequate exporting, and also governmental guarantee and support. These can be concluded by some strategy alternative development of partner pattern, for example, increasing skill and knowledge require by training and education, government require to assist all traditional fisherman by adding capital employed 3) governmental require to arrange partner pattern model and mechanism and also guarantee its execution with orders going into effect to be both party which is have partner to do not each other harming. Wollen Sie im Casino sofort spielen ohne jegliche Einzahlung, werden Sie zahlreiche Optionen auf dieser Seite dazu finden. Einige Boni ohne Einzahlung erhalten Sie nur, wenn Sie Bonus Codes nutzen. Bei den meisten Casinos erhalten Sie den Bonus Code ganz einfach über den Support oder er steht schon in den Bonusbedingungen. Keywords: fishery entrepreneur, traditional fisherman, partner